Pertanggungjawaban Pidana Pelaku Pencucian Uang dalam Perspektif Hukum Pidana Indonesia - Darma Setiawan; Erham; Gufran (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the criminal liability of perpetrators of money laundering under Indonesian criminal law. The research method used is a normative legal approach, involving an examination of relevant legislation and legal literature. The results of the study indicate that the criminal liability of money laundering perpetrators is based on Law No. 8 of 2010 as a special provision and is supported by general provisions in Law No. 1 of 2023 on the Criminal Code regarding criminal liability and the capacity to be held accountable. Its implementation still faces evidentiary challenges, thus requiring strengthened coordination between the Financial Transaction Reports and Analysis Center (PPATK) and law enforcement agencies, as well as enhanced oversight of financial transactions.